Companion Animals Are Spillover Hosts of the Multidrug-Resistant Human Extraintestinal Escherichia coli Pandemic Clones ST131 and ST1193 - Kidsley, Amanda K.; White, Rhys T.; Beatson, Scott A.; Saputra, Sugiyono; Schembri, Mark A.; Gordon, David; Johnson, James R.; O’Dea, Mark; Mollinger, Joanne L.; Abraham, Sam; Trott, Darren J. (Frontiers in Microbiology, 2020)
Escherichia coli sequence types 131 (ST131) and 1193 are multidrug-resistant extraintestinal pathogens that have recently spread epidemically among humans and are occasionally isolated from companion animals. This study characterized a nationwide collection of fluoroquinolone-resistant (FQR) E. coli isolates from extraintestinal infections in Australian cats and dogs. For this, 59 cat and dog FQR clinical E. coli isolates (representing 6.9% of an 855-isolate collection) underwent PCR-based phylotyping and whole-genome sequencing (WGS). Isolates from commensal-associated phylogenetic groups A (14/59, 24%) and B1 (18/59, 31%) were dominant, with ST224 (10/59, 17%), and ST744 (8/59, 14%) predominating. Phylogenetic group D ST38 (8/59, 14%) was also overrepresented, and the virulence-associated phylogenetic group B2 accounted for 12% of isolates (7/59), with ST131 predominating (6/7 isolates, 86%); no ST1193 isolates were identified. In a WGS-based comparison with 188 reference human and animal ST131 isolates, 20 cat and dog-source ST131 isolates were phylogenetically diverse. Although cat and dog-source ST131 isolates exhibited some minor sub-clustering, most were closely related to human-source ST131 strains. Furthermore, the prevalence of ST131 as a cause of FQR infections in Australian companion animals was relatively constant between this study and the 5-year-earlier study of Platell et al. (2010) (9/125 isolates, 7.2%). Thus, although the high degree of clonal commonality among FQR clinical isolates from human versus companion animal suggests the possibility of bi-directional between-species transmission, the much higher reported prevalence of ST131 and ST1193 among FQR clinical isolates from humans compared to companion animals suggests that companion animals are spillover hosts rather than a primary reservoir for these lineages.